KUALITAS PELAYANAN KESEHATAN KELUARGA DAN GIZI MASYARAKAT OLEH DINAS KESEHATAN KOTA PRABUMULIH - Feni Mertiana; Aditia Dwinanto Nugroho; Amancik Amancik; Aswindi Ramadhila; Sri Diana (MAP Program Pascasarjana Universitas Sjakhyakirti, 2022)
This study aims to determine the quality of family health services and community nutrition by the Prabumulih City Health Service. This research was conducted at the Prabumulih City Health Office. This research is a descriptive research with a qualitative approach. Technique Determination of informants using purposive technique. The technique of obtaining data uses several procedures for entering the field, stages when in the field, stages out of the field. Based on the results of the study, it showed that the quality of family health and community nutrition services by the Prabumulih City Health Service, based on aspects of physical appearance, reliability, responsiveness, assurance, empathy had not gone well. The aspects of service quality are not going well, seen from the physical appearance, the availability of physical facilities and equipment has not provided comfort for the patients served; Reliability, regarding the suitability of the services provided with the scheduled information is not consistent, the standard of recording administration services is still convoluted; responsiveness, health services for patients cannot be carried out quickly in accordance with patient needs and expectations. The patience and hospitality of the nurses were not good; empathy / empathy doctors and nurses do not understand and pay attention to the feelings of patients being served. Nurses and doctors in serving patients have not reflected a sincere attitude, and are less consistent with respect to the suitability and timeliness of serving patients. Suggestions that can be given are the need for additional medical personnel, the existence of services and the provision of complete drugs as needed by patients, as well as the existence of information media that clearly contains procedures and procedures for providing services to patients.